Factors associated with willingness to take up indoor residual spraying to prevent malaria in Tororo district, Uganda: a cross-sectional study - Ignatius Wadunde; Arthur Mpimbaza; David Musoke; John C. Ssempebwa; Michael Ediau; Doreen Tuhebwe; Yeka Adoke; Rhoda K. Wanyenze (Malaria Journal, 2018)
Abstract Background Indoor residual spraying (IRS) is an efficient method of preventing malaria in homes, and community willingness to take up IRS is critical to its success. The first phase of IRS was conducted in Tororo district, Uganda between December 2014 and January 2015. High coverage rates (90%) were attained in the district. However, Mulanda sub-county had the lowest coverage of 78%, in the first round. This study assessed willingness and associated factors of IRS uptake among household heads for the next IRS campaign in Mulanda sub-county, Tororo district. Methods A household survey was conducted in all three parishes of Mulanda sub-county. A multistage sampling technique involving the village and household as the first and second sampling levels, respectively, was used to identify 640 households Household heads were interviewed using standard questionnaire. Seven key informants were also conducted to explore the impact of community IRS-perceptions on uptake. Bi-variable and multi-variable logistic regression analyses were used to identify factors associated with willingness to take up IRS. Qualitative data was analysed by thematic content analysis method. Results Most (79.9%) respondents were willing to take up repeat IRS. However this was below the target of 85%. Fear of insecticide adverse effects (62%) was the most common reason mentioned by 134 (21%) household heads who were not willing to take up IRS. Factors associated with to take up IRS were; age ≥ 35 years (AOR 1.9; 95% CI 1.08–3.51), higher socio-economic status (AOR 0.4; 95% CI 0.27–0.98), not taking IRS in previous round (AOR 0.1; 95% CI 0.06–0.23), not knowing reason for conducting IRS (AOR 0.4; 95% CI 0.24–0.78) and having an iron sheet roof (AOR 2.2; 95% CI 1.03–4.73). Community and religious leaders were the preferred sources of IRS information. Conclusions The level of willingness to take up IRS was low (79%) compared to the targeted 85%. Involvement of community and religious leaders in community sensitization on the efficacy and safety of the chemicals could increase uptake of IRS.